Comparative genomic and transcriptome analyses of pathotypes of Xanthomonas citri subsp. citri provide insights into mechanisms of bacterial virulence and host range - Jalan, Neha; Kumar, Dibyendu; Andrade, Maxuel O.; Yu, Fahong; Jones, Jeffrey B.; Graham, James H.; White, Frank F.; Setubal, João C.; Wang, Nian (My University, 2013)
Background: Citrus bacterial canker is a disease that has severe economic impact on citrus industries worldwide and is caused by a few species and pathotypes of Xanthomonas. X. citri subsp. citri strain 306 (XccA306) is a type A (Asiatic) strain with a wide host range, whereas its variant X. citri subsp. citri strain Aw12879 (Xcaw12879, Wellington strain) is restricted to Mexican lime. Results: To characterize the mechanism for the differences in host range of XccA and Xcaw, the genome of Xcaw12879 that was completed recently was compared with XccA306 genome. Effectors xopAF and avrGf1 are present in Xcaw12879, but were absent in XccA306. AvrGf1 was shown previously for Xcaw to cause hypersensitive response in Duncan grapefruit. Mutation analysis of xopAF indicates that the gene contributes to Xcaw growth in Mexican lime but does not contribute to the limited host range of Xcaw. RNA-Seq analysis was conducted to compare the expression profiles of Xcaw12879 and XccA306 in Nutrient Broth (NB) medium and XVM2 medium, which induces hrp gene expression. Two hundred ninety two and 281 genes showed differential expression in XVM2 compared to in NB for XccA306 and Xcaw12879, respectively. Twenty-five type 3 secretion system genes were up-regulated in XVM2 for both XccA and Xcaw. Among the 4,370 common genes of Xcaw12879 compared to XccA306, 603 genes in NB and 450 genes in XVM2 conditions were differentially regulated. Xcaw12879 showed higher protease activity than XccA306 whereas Xcaw12879 showed lower pectate lyase activity in comparison to XccA306. Conclusions: Comparative genomic analysis of XccA306 and Xcaw12879 identified strain specific genes. Our study indicated that AvrGf1 contributes to the host range limitation of Xcaw12879 whereas XopAF contributes to virulence. Transcriptome analyses of XccA306 and Xcaw12879 presented insights into the expression of the two closely related strains of X. citri subsp. citri. Virulence genes including genes encoding T3SS components and effectors are induced in XVM2 medium. Numerous genes with differential expression in Xcaw12879 and XccA306 were identified. This study provided the foundation to further characterize the mechanisms for virulence and host range of pathotypes of X. citri subsp. citri.
Citation: Jalan, N., . . . & Wang, N. (2013). Comparative genomic and transcriptome analyses of pathotypes of Xanthomonas citri subsp. citri provide insights into mechanisms of bacterial virulence and host range. BMC Genomics, 14(1), 551-568. https://doi.org/10.1186/1471-2164-14-551
Keywords: Xanthomonas citri; Wellington strain; Citrus canker; HR; Virulence; Transcriptome; RNA-Seq